Retrospective Assessment of Malnutrition among Under-five Children in Ayder Referral Hospital, Tigray Ethiopia - Teklemariam Gultie; Desta Mebrahtu; Girum Sebsibie (Intelektual Pustaka Media Utama, 2015)
Currently worldwide there are about 60 million children with moderate acute and 13 million with severe acute malnutrition. About 9% of sub-Saharan African and 15%of south Asian children have moderate acute malnutrition and about 2% of children in developing countries have severe acute malnutrition. The objective of aim the study was to assess the magnitude of malnutrition in under five children in Ayder referral hospital using a retrospective cross-sectional study design. This study showed that male children, 168(58.1%), were higher than female, 121(41.9%).. Majority, 133(46%), were in the age group b/n 12 to 24 months .More than half, 186(64.4%) were rural dwellers. The types of malnutrition identified were Marasmus, kwashiorkor, Marasmic kwash and underweight which account for 116(40.1%), 69(23.9%), 54(18.7%) and 50(17.5%) respectively. Marasmus was the predominant type of malnutrition in all age groups of under five malnourished children with prevalence of 40.1% where as underweight was the prevalent type of malnutrition (17.3%). More over the infant feeding practices such as exclusive breast feeding, timely initiation of complementary feeding, and having history of breast feeding once in their life during infancy were relatively higher among the children as compared with other studies.